Loss of Purkinje cells in the PKCgamma H101Y transgenic mouse - Yunong, Zhang; Snider, Adam; Willard, Lloyd; Takemoto, Dolores J.; Lin, Dingbo (My University, 2010)
Spinocerebellar ataxia type 14 (SCA14) is an autosomal, dominant neurodegenerative disorder caused by mutations in PKCγ. The objective of this study was to determine effects of PKCγ H101Y SCA14 mutation on Purkinje cells in the transgenic mouse. Results demonstrated that wild type PKCγ-like Purkinje cell localization of HA-tagged PKCγ H101Y mutant proteins, altered morphology and loss of Purkinje cells were observed in the PKCγ H101Y SCA14 transgenic mouse at four weeks of age. Failure of stereotypical clasping responses in the hind limbs of transgenic mice was also observed. Further, PKCγ H101Y SCA14 mutation caused lack of total cellular PKCγ enzyme activity, loss of connexin 57 phosphorylation on serines, and activation of caspase-12 in the PKCγ H101Y SCA14 transgenic mouse. Results clearly demonstrate a need for PKCγ control of gap junctions for maintenance of Purkinje cells. This is the first transgenic mouse to our knowledge which models a human SCA14 mutation.
Keywords: Protein kinase C gama; Spinocerebellar ataxia type 14; Purkinje cell; Gap junctions; Endoplasmic reticulum stress; Apoptosis